2017
DOI: 10.5334/gjgl.109
|View full text |Cite
|
Sign up to set email alerts
|

Quantifier spreading in child eye movements: A case of the Russian quantifier <i>kazhdyj</i> ‘every'

Abstract: Extensive cross-linguistic work has documented that children up to the age of 9-10 make errors when performing a sentence-picture verification task that pairs spoken sentences with the universal quantifier every and pictures with entities in partial one-to-one correspondence. These errors stem from children's difficulties in restricting the domain of a universal quantifier to the appropriate noun phrase and are referred in the literature as quantifier-spreading (q-spreading). We adapted the task to be performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Suppose there are three girls and four elephants and each of the three girls is riding a different elephant; one of the elephants does not have a girl riding on it, but this fact is irrelevant to the true claim that every girl is riding an elephant . However, children, L2 learners, and heritage speakers will sometimes reject the claim and give as their justification the elephant without a girl on its back; baseline adults accept the claim (see Brooks & Braine, 1996; Crain, Thornton, Boster, Conway, Lillo-Martin & Woodams, 1996; Sekerina & Sauermann, 2017, for child learners; Carpini, 2003; Berent, Kelly & Schueler-Choukairi, 2009, for adult L2 learners, and Sekerina & Sauermann, 2015, for English-dominant heritage speakers of Russian). While in children it might be the case that knowledge of quantification is still developing in tandem with executive function (i.e., the ability to correctly attend to relevant elements of the task), in adults – both L2 learners and heritage speakers – this explanation appears untenable.…”
Section: What Are Heritage Languages and Who Are Their Speakers?mentioning
confidence: 99%
“…Suppose there are three girls and four elephants and each of the three girls is riding a different elephant; one of the elephants does not have a girl riding on it, but this fact is irrelevant to the true claim that every girl is riding an elephant . However, children, L2 learners, and heritage speakers will sometimes reject the claim and give as their justification the elephant without a girl on its back; baseline adults accept the claim (see Brooks & Braine, 1996; Crain, Thornton, Boster, Conway, Lillo-Martin & Woodams, 1996; Sekerina & Sauermann, 2017, for child learners; Carpini, 2003; Berent, Kelly & Schueler-Choukairi, 2009, for adult L2 learners, and Sekerina & Sauermann, 2015, for English-dominant heritage speakers of Russian). While in children it might be the case that knowledge of quantification is still developing in tandem with executive function (i.e., the ability to correctly attend to relevant elements of the task), in adults – both L2 learners and heritage speakers – this explanation appears untenable.…”
Section: What Are Heritage Languages and Who Are Their Speakers?mentioning
confidence: 99%
“…Sekerina and Sauermann (2017) also report increased looks to the extra object accompanying children's Q-spreading errors.…”
mentioning
confidence: 88%
“…In related work, Donaldson and Lloyd (1974) found that 4year-old children treated the sentence, "All the cars are in the garages" as entailing that "All the garages have cars in them" indicating a symmetry requirement (see also Donaldson & McGarrigle, 1974, for a more widely available report of this phenomenon). Since these early studies, many additional studies have investigated this phenomenon, positing a range of semantic, pragmatic, and syntactic explanations, many as recent as the past 2-3 years (for very recent ideas, see Brunetti et al, 2021;Chen, Rosenstein & Hackl, 2020;Denić & Chemla, 2020;Drozd et al, 2019;Ke & Gao, 2020;Kiss, & Zétényi, 2017;Sekerina, & Sauermann, 2017; see Brooks & Parshina, 2019 for review). In the present study, we present evidence in favor of a form of pragmatic account, and show that children's apparent errors arise when experimenters fail to adequately specify a clear "Question Under Discussion" (henceforth QUD; Roberts, 1996Roberts, /2012.…”
Section: Introductionmentioning
confidence: 99%